2019
DOI: 10.3390/ijms20215334
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Protocol to Obtain Transgenic Coffee, Coffea arabica L., Expressing the Cry10Aa Toxin of Bacillus thuringiensis

Abstract: This report presents an efficient protocol of the stable genetic transformation of coffee plants expressing the Cry10Aa protein of Bacillus thuringiensis. Embryogenic cell lines with a high potential of propagation, somatic embryo maturation, and germination were used. Gene expression analysis of cytokinin signaling, homedomains, auxin responsive factor, and the master regulators of somatic embryogenesis genes involved in somatic embryo maturation were evaluated. Plasmid pMDC85 containing the cry10Aa gene was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Typica with a high potential of propagation, plantlet conversion and genetic transformation. Three months were required to induce the development of SEs to be ready for stable genetic transformation 8 . Briefly, this protocol was followed: leaf explants of coffee cultured in callus induction medium (CIM medium, Van Boxtel et al 14 ) provided proembryogenic masses (PEM) obtained after one month with 93% efficiency of cultivated explants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Typica with a high potential of propagation, plantlet conversion and genetic transformation. Three months were required to induce the development of SEs to be ready for stable genetic transformation 8 . Briefly, this protocol was followed: leaf explants of coffee cultured in callus induction medium (CIM medium, Van Boxtel et al 14 ) provided proembryogenic masses (PEM) obtained after one month with 93% efficiency of cultivated explants.…”
Section: Resultsmentioning
confidence: 99%
“…SE induced from leaf explants has been the most widely used target tissue in coffee micropropagation and stable genetic transformation 1 . Published protocols have shown that SE induction and proliferation is time consuming, ranging from 9 to 20 months until they can be used for stable genetic transformation 8 , 20 , 21 . In most of these reports, SE regeneration to plants in C. arabica has been shown to be more difficult and time consuming than in C. canephora P .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The article by Valencia-Lozano [11] is another paper on coffee (Coffea arabica). It demonstrates an efficient protocol that enables the particle bombardment-mediated stable genetic transformation of coffee plants that express the Cry10Aa protein of Bacillus thuringiensis (Bt) for the first time.…”
mentioning
confidence: 99%